Republic of Poland : Final Country Procurement Assessment Report, Volume I. Findings and Recommendations - World Bank (Washington, DC, 2013)
From the legislative point of view, Poland has a relatively developed public procurement system, though, as recorded above, further improvements remain necessary. Since June 1994, when the Sejm passed the first public procurement law, the law has gone through several amendments with a view to incorporating the lessons learned by the OPP and procuring entities. The law has been revised again in order to make it compatible with the EU procurement directives. It is expected that this revision will further improve the transparency and competitiveness provided by the current law. Furthermore, during the last five years, procuring entities in Poland, especially at the national level, have acquired experience in implementing procurement according to the requirements of the public procurement law, and the Office of Public Procurement in supporting these entities in their responsibility of conducting public procurement and in supervising the system. However, it has been determined that in most cases the shortcomings relate to practice and only in a few cases to the deficiency of the procedures. Therefore, while it is important to make the law more transparent and competitive, to realize savings in public spending, improvement in procurement practices need an even sharper focus. The areas to be addressed are: Provide good quality standard bidding documents. Introduce unambiguous and neutral technical specifications. Introduce objective evaluation criteria. Separate evaluation of bidder's qualification from the bid evaluation. Require bid opening the same day as the deadline for bid submission. Allow adequate bid preparation time to bidders. Remove barriers to participation by foreign bidders. Require mandatory post-qualification in the absence of pre-qualification. Allow adequate time to procuring entities to spend budget allocations. Build procurement as a distinct profession. Introduce two-tier procurement decision making system. Introduce code of ethics for procurement professionals. Include provisions in the law suitable for procurement of consultant services. Prepare a training strategy and implement it. Improve bid dispute arbitration procedures. Introduce procedures for procurement under Euros 3,000 to minimize the use of Sole Sourcing. Introduce best practices to procuring entities through the Public Procurement Bulletin.